Trends and factors influencing the mental health of college students in the post-pandemic: four consecutive cross-sectional surveys - Chen, Yinhai; Ke, Xiong; Liu, Jinfeng; Du, Jun; Zhang, Jiali; Jiang, Xuan; Zhou, Tong; Xiao, Xiao (Frontiers in Psychology, 2024)
Background: The long-term impact of COVID-19 on the mental health and well-being of college students, specifically trends over time after full removal of COVID-19 restrictions, has not been well-studied.Methods: Four consecutive cross-sectional surveys were conducted in December 2022 (N=689), March 2023 (N=456), June 2023 (N=300), and November 2023 (N=601) at a university in Sichuan Province, China.The proportion of students with COVID-19 panic decreased from 95.1% to 77.3% (P < 0.001). The prevalence of moderate anxiety and above decreased from 18% to 13.6% (P < 0.001), and the prevalence of moderate and above depression decreased from 33.1% to 28.1% (P < 0.001), while the prevalence of post-traumatic stress disorder (PTSD) increased from 21.5% to 29.6% (P < 0.005). Further, the proportion of suicidal thoughts increased from 7.7% to 14.8% (P < 0.001). Suicidal thoughts and self-injuries were significantly associated with COVID-19 panic, depression, anxiety, and PTSD. Students who reported being in close contact with COVID-19 patients in the past were more likely to develop PTSD. Further, COVID-19-induced panic was a risk factor for self-injury.One year after the COVID-19 pandemic, the overall mental health of college students was not optimal. Hence, we can conclude that the long-term impacts of COVID-19 on the mental health of college students may have already occurred. To mitigate this impact and prepare for the next major public health event, strengthening college students' mental health curricula and promoting healthy behaviors among college students should be a priority for universities and education authorities.